Synthesis and characterisation of CU (II) schiff base complex derived from Amoxicillin Trihydrate and Vanillin for antimicrobial application - AVILA JOSEPHINE.B; MARY TERESITA.V; ASHWINI ANANTHARAMAN; RAJASEKAR.T; JERRINE JOESPH (International Journal of Pharma and Bio Sciences, 2017)
A new metal (II) complex of Schiff base were synthesized from the novel ligand 6-(2-(4-hydroxy-3-methoxybenzylibeneamino)-2-(4-hydroxyphenyl)acetamido)-3,3-dimethy 7oxo 4-thia-1-aza bicycle[3.2.0] heptane-2-carboxylic acid(BAAMOTACA) derived from amoxicillin trihydrate and vanillin and the Schiff base is orange colour solid and having sharp melting point. The metal complex was investigated using spectroscopic techniques IR, 1H NMR and magnetic measurements. Antibacterial and Antifungal activity of the of Cu (II) Schiff base was done using Agar well diffusion methods. The IR spectra illustrated a bidentate ligand which coordinates through phenolic oxygen atom and imino nitrogen atom from azomethine bond. In 1H NMR the azomethine proton signals in the spectrum of the Cu-BAAMOTACA (Cu-B) complex is shifted downfield. The molecular weight of the ligand was confirmed by GC-MS analysis and the retention time of the complex was found to be 17.27. The electron paramagnetic resonance spectral lines exhibited tetragonal distortion from axial symmetry, with gÇÇ>g⊥ in the copper (II) complexes with diamagnetic behaviour.It may find a strong position in development of new pharmaceuticals especially as antibacterial and antifungal agents.